A Practical Guide to High‐resolution X‐ray Spectroscopic Measurements and their Applications in Bioinorganic Chemistry. Issue 9 (21st July 2016) - Kowalska, Joanna K.; Lima, Frederico A.; Pollock, Christopher J.; Rees, Julian A.; DeBeer, Serena
Abstract: The bioinorganic chemistry community has had a long history of utilizing a diverse range of spectroscopic techniques to obtain detailed geometric and electronic structural insights into metalloprotein active sites. In recent years, the development of beamlines optimized for high‐resolution X‐ray spectroscopy has provided novel tools for the elucidation of biological active site structures. These methods include both non‐resonant and resonant X‐ray emission spectroscopy. Herein, we briefly introduce both X‐ray absorption and X‐ray emission spectroscopy, and the added information that can be obtained through high‐resolution measurements. The information content of each spectroscopic approach, as well as the required instrumentation, is discussed. Applications of these methods in bioinorganic chemistry are highlighted. Abstract :